Xenophon on Emotions in the "Symposium" and the "Apology" - Zaborowski, Robert (Polskie Towarzystwo Filologiczne, 2020)
After presenting the reasons for undertaking an analysis of the Symposium and the Apology with regard to emotions, I focus on the groups of pleasure/joy and love/friendship and discuss relevant contexts. They provide us with a complex picture which I then try to interpret by means of a concept of hierarchy. Next, I touch upon on the issue of the expression of emotions. Finally I show why and how the Symposium and the Apology may be helpful in the study of emotions.